Managing financial crises in emerging market economies - experience with the involvement of private sector creditors - Christian Thimann; Regine Wölfinger; Thierry Bracke; Rita Bessone Basto; Ole Hollensen; Stephan von Stenglin; Santiago Fernández de Lis; Pierre-François Weber; Marco Committeri; Rolf Pauli; Christian Just; Minna Nikitin; et al. (European Central Bank (ECB), 2005)
Ensuring the involvement of private sector creditors in the resolution of sovereign debt crises is crucial to ensure an effective management and orderly resolution of those crises. A review of experience gained in past financial crises suggests that crisis management practices have been largely following a case-by-case approach. This has led to some uncertainty about how the official sector addresses different types of crises, which in turn might partially account for the very mixed results achieved so far. From a global welfare perspective, the resolution of international financial crises is too costly and takes too long. Efforts to improve predictability of crisis resolution processes – through guiding debtor, creditor and official sector behaviour – could lower overall costs of such crises and bring about a better distribution of these costs. Past experience with such private sector involvement shows that, in certain cases, existing instruments have successfully contributed to minimising the economic disruptions caused by crises. However, the effective use of these instruments requires predictable and strong commitment of all parties involved. Key variables in that regard are the country's economic fundamentals and its track record prior to the crisis, underscoring the importance of effective surveillance and crisis prevention. Success also hinges on the country's resolve to implement necessary domestic adjustment measures. A transparent process providing for early dialogue between a debtor and its creditors also facilitates private sector involvement. Finally, the IMF plays a key role in crisis situations, as accurate and timely diagnosis by the IMF helps identify at an early stage the need for private sector involvement.
Keywords: F33; F34; 330; Sovereign default; bond restructuring; emerging markets; financial crises; moral hazard; international financial architecture.; Finanzsektor; Privatwirtschaft; Gläubiger; Schwellenländer; Finanzkrise